An exploration of low- and high-immersive virtual reality modalities for willingness to communicate in English as a second language - Anastassiya Yudintseva (Computers & Education: X Reality)
This mixed-method quasi-experimental study compares the impact of two different kinds of virtual reality environments on the willingness of English as a Second Language (ESL) students to engage in communication. Twenty high-level ESL graduate students were recruited for the research and organized into 10 pairs. Each pair of students completed two separate speaking tasks. One task took place in a low-immersive virtual reality environment, while the other task took place in a high-immersive virtual reality environment. The study was counterbalanced, with half completing the two tasks in one order, while the other half completed them in the reverse order. The study found no statistically significant differences between the modality conditions on willingness to communicate. Task order and action-oriented instructional methods were found to have greater impact than the modality. However, a significant difference was found between participants' affective-cognitive experiences, with participants reporting higher cognitive load and greater enjoyment in high-immersive condition. Speaking anxiety was also reduced after participation in two virtual reality tasks, leading to an increase in self-confidence. Additionally, qualitative analysis identified relationships between various technological, affective-cognitive, and individual factors that can affect the student's willingness to communicate. Empirical and theoretical implications are discussed, along with limitations and directions for future research.